2015
DOI: 10.1177/0009922814567305
|View full text |Cite
|
Sign up to set email alerts
|

A Balanced Protocol for Return to School for Children and Youth Following Concussive Injury

Abstract: A balance of cognitive rest and timely return to school need to be considered for returning any student to school after a concussion. Implementation of these new recommendations may be an important tool in prevention of prolonged absence from school and academic failure while supporting brain recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
73
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(73 citation statements)
references
References 54 publications
0
73
0
Order By: Relevance
“…Accommodations for students with recognized educational and medical needs, including concussion, may include either formally defined and temporary individualized health care plans, 504 plans, and individualized education plans, or informal academic accommodations provided by individual educators . Current guidelines for accommodating students returning to school after concussion do not consider how school policies or teacher education on RTL practices might affect RTL guideline implementation or fidelity.…”
mentioning
confidence: 99%
“…Accommodations for students with recognized educational and medical needs, including concussion, may include either formally defined and temporary individualized health care plans, 504 plans, and individualized education plans, or informal academic accommodations provided by individual educators . Current guidelines for accommodating students returning to school after concussion do not consider how school policies or teacher education on RTL practices might affect RTL guideline implementation or fidelity.…”
mentioning
confidence: 99%
“…Although the proportion of PPCS development in this study is within the range observed among populations who present to pediatric tertiary concussion clinics [4,28], it is slightly higher than rates observed in previous studies examining academic outcomes among patients evaluated in the emergency department setting [17,25]. Although students with PPCS did not perform significantly worse academically than those who did not subsequently develop PPCS, the clinical manifestations of PPCS (e.g., vestibulo–ocular dysfunction, migraine headaches, postinjury psychiatric outcomes) may present unique challenges that impact school functioning and quality of life over a longer period of time, and thus warrant further investigation [29,30]. …”
Section: Discussionmentioning
confidence: 97%
“…On one hand, there is a need to prevent the worsening of concussion symptoms by over stimulating a concussed brain [12,13] and on the other, time out of school may increase the potential production of anxiety from missing school [10,14].…”
Section: Introductionmentioning
confidence: 99%
“…The management of concussion for adolescents as athletes has been described and is routinely recognized through the establishment of "Return to Play" (RTP) guidelines [8], however, limited attention has been given to the management of adolescents as students returning to the school environment, or "Return to Learn" (RTL) [9,10]. Specifically, research addressing the resumption of typical school participation in relation to the resumption of participation in sports remains lacking.…”
mentioning
confidence: 99%